INSTITUTIONAL, STRATEGIC AND SOCIO-POLITICAL FACTORS IN THE DEVELOPMENT OF GREEN POLITICAL PARTIES IN SERBIA - Stojanovic, Igor (Political Review, 2026)
This paper examines how institutional (electoral) design, in interaction with party strategies and the broader social context, shapes the parliamentary affirmation of green political parties in Serbia. Drawing on contemporary approaches that do not interpret the development of issue-oriented parties through institutional determinism, but rather through the interplay of structural rules, strategic positioning, and social mobilization, the study analyzes the role of the proportional electoral system as one of the dominant factors of their political relevance. Particular attention is devoted to the elements of electoral engineering in Serbia—a single nationwide electoral district, the electoral threshold, the D’Hondt formula, and closed party lists—and their cumulative effects under conditions of post-transitional party competition. The empirical analysis covers electoral processes and key reforms of electoral legislation in the period 1990–2023, with particular emphasis on the introduction of the proportional representation system in 1992. The methodology combines quantitative analysis of disproportionality and party system fragmentation (the Gallagher Index and the Effective Number of Parties Index) with qualitative analysis of coalition strategies, processes of institutionalization, and contextual social conflicts that enabled the political articulation of green issues.The findings indicate that the proportional electoral system in Serbia provides structural opportunities for the entry of green political parties into parliament, but that their sustained parliamentary relevance depends on the ability of green actors to strategically consolidate support and politically articulate social and environmental conflicts. The paper thus demonstrates that the rise of green actors is the result of the interaction between institutional rules, their quantitative effects, and strategic agency within a specific social context.